Who gets it? Explaining variability in children’s written irony comprehension - Olkoniemi, Henri; Häikiö, Tuomo; Laine, Matti; Pexman, Penny M. (Cambridge University Press (CUP), 2026)
Understanding verbal irony involves detecting that the speaker’s intended meaning contrasts with the literal meaning. This is challenging for children as the underlying skills required to understand irony may not be fully developed. We investigated how 10-year-olds’ working memory, empathy skills, and gender were related to their processing and comprehension of written irony. Data from two previous eye-tracking experiments with 97 children (46 girls and 51 boys) were analysed. Results showed that children with stronger empathy skills had higher irony comprehension accuracy and were less likely to reread ironic phrases. Higher working memory was linked to faster processing of irony but did not lead to higher comprehension. Conversely, lower working memory was associated with more accurate irony comprehension. Child gender was not related to irony comprehension. These results imply that working memory and emotional perspective-taking are important for children’s irony comprehension, underscoring theories that take individual differences into account.